The Existence Of The Police Of The Republic Of Indonesia In Managing Anarchic Actions On Haruku Island - Titahelu, Juanrico Alfaromona Sumarezs (Sawerigading Law Journal, 2022)
Indonesia is a country that adheres to a democratic system, so the position of the people occupies the highest position.In various places in the world there are conflicts and even violence between groups. One of them, namely Maluku, is currently dealing with several cases of conflict between groups or countries, including residents of Kariu and residents of the Ori hamlet, which started from a verbal argument between two residents of Kariu and residents of the hamlet. Geographically, the country of Kariu borders Pelau and Ori, in terms of the anatomy of the problem, this crime involves people in the sense of the person of the perpetrator and the victim. Anarchy is a physical disorder in civil society in the form of clashes, mass fights, killings, looting, and destruction of public facilities and infrastructure, as well as private or other non-criminal facilities. According to the "Regulation of the Chief of Police Number 1/X/2010 concerning Overcoming Anarchy, police officers gradually deal with appeals, with bare hands, blunt weapons/chemical weapons/tear gas, warning shots, paralyzing shots with rubber bullets and in emergency situations using live ammunition. The handling by the police (brimob) against anarchic actions on the island of Haruku include the following: Conduct legal guidance and counseling to the community on Haruku Island Conduct coaching and training for members of the police on procedures for handling anarchic acts committed by certain groups. Carrying out a guard consisting of 3 zones, namely the green zone, yellow zone, and red zone; and If a violation occurs, then the member of the police who commits the violation can be processed and given sanctions in accordance with the rule of law.